Investigating interactions: how do doctors and patients experience the disclosure of significant information in the advanced cancer setting and how do these experiences enhance practice? - Furber, Lynn (2010)
This thesis focuses specifically on the transmission of bad news from doctors to patients and their families in the context of a hospital oncology department. It uses awareness context theory as a basis for exploring communication between patients and health care professionals, particularly when the information to be disclosed is sensitive and will have a significant bearing on how people perceive their future. In order to enhance clinical practice, senior health care professionals in particular, have in the past been encouraged through government policy and professional legislation to attend communication skills courses to develop the way they communicate and interact with patients. Yet, in spite of these interventions evidence suggests that doctors and other health care professionals still find it difficult to negotiate sensitive and emotionally challenging discussions, and frequently question whether or not patients are aware and understand the information disclosed to them and whether or not information provided meets the needs and expectations of patients.